Effect of temperature variations on the fabrication of SLS-Na2CO3-ES-P2O5-CaF2-Al2O3 based bioglass-ceramics - Ismail, Nur Quratul Aini; Sa’at, Nor Kamilah; Mohd Zaid, Mohd Hafiz; Zainuddin, Norhazlin; Mayzan, Mohd Zul Hilmi (Springer, 2024)
Melt-quenching bioglass-ceramics with the following chemical composition have been prepared 44SLS11Na2CO324ES6P2O56CaF29Al2O3 (wt%). The bioglass-ceramics were sintered at 650 °C, 750 °C, 850 °C, and 950 °C. The aim was to identify the optimal sintering temperature before glass crystallization. The physical properties were characterized by density and linear shrinkage. To characterize the structure properties, X-ray diffraction (XRD), scanning electron microscopy (SEM), and Fourier transform infrared spectroscopy (FTIR) were utilized. The high composition of Si and Ca in soda lime silica (SLS) glass and eggshells (ES), respectively, encourage the utilization of waste materials in the production of bioglass-ceramics. The results showed that at a sintering temperature of 950 °C, the crystallization of fluorapatite was the main phase. Moreover, the high density and optimum linear shrinkage were obtained as the sintering temperature increased. Additionally, grain growth and densification took place at this temperature. The compressive strength of bioglass-ceramics is influenced by sintering temperature and the optimal compressive strength is 136.58 MPa. © Australian Ceramic Society 2024.